2021
DOI: 10.1016/j.aninu.2021.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Arginine promotes myogenic differentiation and myotube formation through the elevation of cytoplasmic calcium concentration

Abstract: This study aimed to explore the mechanism underlying arginine-promoted myogenesis of myoblasts. C2C12 cells were cultured with a medium containing 0.1, 0.4, 0.8, or 1.2 mmol/L arginine, respectively. Cell proliferation, viability, differentiation indexes, cytoplasmic Ca 2+ concentration, and relative mRNA expression levels of myogenic regulatory factors (MRF) and key Ca 2+ channels were measured in the absence or presence of 2 chemical inhibitors, dantrolene (DAN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Previous studies showed that l -Arg could induced C2C12 myoblasts differentiation. Therefore, in this study, we used differentiated C2C12 cells [ 34 , 35 ]. The different concentrations of l -Arg were used to treat LPS-induced C2C12 myotube cells, to explore the mechanism of l -Arg alleviating oxidative stress and apoptosis, and to provide a new idea for alleviating muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that l -Arg could induced C2C12 myoblasts differentiation. Therefore, in this study, we used differentiated C2C12 cells [ 34 , 35 ]. The different concentrations of l -Arg were used to treat LPS-induced C2C12 myotube cells, to explore the mechanism of l -Arg alleviating oxidative stress and apoptosis, and to provide a new idea for alleviating muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal circumstances, arginine functions as a physiological fusogen that facilitates the merger of myoblasts as well as the fusion of intra and extracellular vesicles in the CNS ( Das et al., 2004 ; Koike and Jahn, 2019 ; Gong et al., 2021 ). The positively charged guanidinium side chains, a unique characteristic of this amino acid, pierce cell membranes, forming pores that may facilitate both viral uptake and pTau egress ( Walrant et al., 2017 ; Nyenhuis et al., 2021 ).…”
Section: Cell-cell Fusion the Molecular Actorsmentioning
confidence: 99%
“…The concentration of 0.4 mM arginine in the control group was the concentration of arginine contained in the growth medium (high-glucose DMEM medium) without additional arginine. The concentrations of 1.2 mM and 3.6 mM arginine in the treatment group were in reference to the dosages of arginine treated with the C2C12 cell line in other studies [ 16 , 24 , 25 ]. Consistent with cell morphology ( Figure 5 A), Arg significantly promoted the mRNA expression of myomarker ( Figure 5 D), suggesting Arg can promote myoblast myotube fusion.…”
Section: Resultsmentioning
confidence: 99%
“…When the cells reached 90% confluency, DMEM with 2% horse serum (HyClone, Logan, UT, USA) was added for 6 days to induce myoblast differentiation into myotubes. On day 1 of differentiation, treating C2C12 with 1.2 mM or 3.6 mM of arginine for 72 h. The dosage of arginine was in reference to other studies [ 16 , 24 , 25 ]. On days 0, 2, and 4 of differentiation, DMSO or 1 μM of rapamycin (Beyotime, Shanghai, China) was added to the complete medium to culture the cells.…”
Section: Methodsmentioning
confidence: 99%